Furniture: an analysis of Negeri Sembilan traditional kitchen design / Mohamad Hanif Abdul Wahab, Mohamad Awang and Nor Aniswati Awang Lah - Abdul Wahab, Mohamad Hanif; Awang, Mohamad; Awang, Nor Aniswati (Research Management Institute (RMI), 2013)
The purpose of this research is to proof the exist of furniture in the kitchen of Negeri Sembilan traditional house. The furniture is essential to determine the lifestyle, environment and social activities. Studies on the origins of the Malays enable us to understand the background and social life of traditional Malay, which eventually led to their civilization. Data analysis focused on kitchen area in Negeri Sembilan traditional houses since it is the most active area in the house. The definition of furniture through an interview with experts plays an important role in defining furniture categories, types and usage. The significant activities in the kitchen analyzed to define the furniture function. In conclusion, Malay furniture exist in the kitchen of traditional Negeri Sembilan house and categorize into three functions - body-supporting unit, storage/utility and tool. The furniture designed into two types - loose item and built-in with house structure. The furniture are a simple form, and the design is direct to the basic needs of user and kitchen function.